Conditional Deletion of the V-ATPase a2-Subunit Disrupts Intrathymic T Cell Development - Peterson, Theodore V.; Jaiswal, Mukesh K.; Beaman, Kenneth D.; Reynolds, Joseph M. (Frontiers in Immunology, 2019)
Proper orchestration of T lymphocyte development is critical, as T cells underlie nearly all responses of the adaptive immune system. Developing thymocytes differentiate in response to environmental cues carried from cell surface receptors to the nucleus, shaping a distinct transcriptional program that defines their developmental outcome. Our recent work has identified a previously undescribed role for the vacuolar ATPase (V-ATPase) in facilitating the development of murine thymocytes progressing toward the CD4+ and CD8+ αβ T cell lineages. Vav1Cre recombinase-mediated deletion of the a2 isoform of the V-ATPase (a2V) in mouse hematopoietic cells leads to a specific and profound loss of peripheral CD4+ and CD8+ αβ T cells. Utilizing T cell-restricted LckCre and CD4Cre strains, we further traced this deficiency to the thymus and found that a2V plays a cell-intrinsic role throughout intrathymic development. Loss of a2V manifests as a partial obstruction in the double negative stage of T cell development, and later, a near complete failure of positive selection. These data deepen our understanding of the biological mechanisms that orchestrate T cell development and lend credence to the recent focus on V-ATPase as a potential chemotherapeutic target to combat proliferative potential in T cell lymphoblastic leukemias and autoimmune disease.